Mechanical and Durability Properties of Cementitious Composites with Coconut Fiber and Saw Dust Ash as Partial Cement Replacement - Thu, Phan Thi Anh; Dang, Vo Pham Khanh (Journal of Progress in Civil Engineering, 2025)
Normally cement bricks are widely used for making temporary and permanent civil structures. The aim of this study is to find out the utilization of Saw Dust Ash as a construction material in civil engineering works as a partial replacement of cement. The mix ratio of cement and sand is 1: 5 and water cement ratio of 0.6. Whereas the Coconut fiber is at constant percentage of 0.4% of the volume to be casted. Three range of curing period of 7 days, 14 days and 28 days are considered in the present study of Cement brick with replacement of cement by 0%, 10%, 20% and 30% using Saw Dust Ash (SDA) and Coconut fiber as additive. Mixes with different percentages of SDA are casted. It has been decided to make three different types of conventional specimens with partial replacement of cement with SDA on a percentage of 10%, 20% and 30% in cement brick. Brick mould size 190 x 90 x 90 (mm).